Effect of nanocurcumin (Curcuma longa) on lung histopathology in rats exposed to carbon black - El Roy Achmad Rahmaniabdi; Imam Mustofa; Eka Pramyrtha Hestianah; Widjiati Widjiati; Rochmah Kurnijasanti; Hani Plumeriastuti (Current Biomedicine)
Background Exposure to carbon black can induce respiratory toxicity, leading to tissue remodeling, inflammation, and fibrosis. Curcumin, a compound from Curcuma longa, has been shown to exert protective effects on lung tissue by inhibiting cell proliferation and reducing alveolar epithelial thickening and inflammatory responses.